Ältere Pendelmigranten aus der Türkei: Alters- und Versorgungserwartungen im Kontext von Migration, Kultur und Religion - Strumpen, Sarina (transcript, 2018)
How do assumptions of aging and expectations of care and support change in a world characterized by migration?